Nitrogen doped cuprous oxide as low cost hole-transporting material for perovskite solar cells - Han, Guifang (2020)
Substituting expensive traditional hole transporting material (HTM) with cheaper inorganics is a key factor for perovskite photovoltaics commercialization. Cu2O is a promising p-type semiconductor exhibiting good band-alignment with perovskite. However, due to solvent and temperature incompatibility, Cu2O is typically employed in inverted configuration, where an even more expensive, unstable Phenyl-C61-butyric acid methyl ester is necessary as an electron-transporting layer. Therefore, we explored the use of sputtered nitrogen-doped Cu2O directly on halide-perovskite as a HTM. With a thin interfacial layer, efficiency of 15.73% was achieved. This work indicates the possibility of low cost sputtered inorganics as HTM for efficient perovskite photovoltaics.